The public and private dimensions of a birthday party: Politics, economics, and food in an Amazonian community. Issue 3 (1st October 2016) - Zycherman, Ariela
ABSTRACT: The emergence of the birthday party among the Tsimane' Indians of the Bolivian Amazon is a phenomenon embedded in political economy and connected to larger state initiatives that integrate historically marginalized indigenous peoples into state processes and cash economies, both directly and indirectly. Focusing on the sharing of meals and beverages during the celebration of birthday parties, this article demonstrates two ways in which the public and private lives of the Tsimane' are negotiated. The first concerns the relationships of Tsimane' to the nation by considering their involvement in state and global markets and new forms of Bolivian bureaucracy that led to the formal acknowledgement of individuals' birthdays. The second explores relationships within the community and between households, families, and individuals. This article highlights differences between everyday eating and party eating to discuss the ongoing formulation of modern Tsimane' life.